Investigating food additives - Boersema, Wendy (Lawrenceville, N. J. : Meridian Education Corporation)
This program explains how preservatives, antioxidants, stabilizer, buffers, sulfites, and other food additives work
Executive producer, Twila Sears
Keywords: Food additives; Food preservatives